2011
DOI: 10.1007/s10856-011-4494-1
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of dual-ligand modified chitosan as a liver targeting vector

Abstract: Vector plays an important role in hepatic targeted drug delivery system. In this study, a novel material as a liver targeting vector, dual-ligand modified chitosan (GCGA) composed of chitosan (CTS), glycyrrhetinic acid (GA) and lactobionic acid (LA), was designed and synthesized by an orthogonal experiment with two-step synthesis under mild conditions. The synthesized final product was characterized and confirmed by FTIR and (1)H-NMR spectroscopy, and DS of GA and LA in CTS were measured to be 13.77 and 16.74 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In this study, GA was conjugated to CS via a reaction between the amine group (NH 2 ) of CS and the carboxyl group (COOH) of GA by using 1‐ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide (EDC), and N ‐hydroxysuccinimide (NHS) as activation agents, as described in a previous study . The reaction mechanism of CS–CA synthesis is shown in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, GA was conjugated to CS via a reaction between the amine group (NH 2 ) of CS and the carboxyl group (COOH) of GA by using 1‐ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide (EDC), and N ‐hydroxysuccinimide (NHS) as activation agents, as described in a previous study . The reaction mechanism of CS–CA synthesis is shown in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…198,[255][256][257][258][259][260] In our previous report, dualligand Gal moieties and GA-modified chitosan NPs were prepared as a drug or gene carrier for HCC. 261 The cellular uptake in vitro and biodistribution in vivo demonstrates that this dual-ligand decorated nanosystem can enhance the specific recognition and internalization by hepatoma cells, compared with single-ligand decorated nanosystem. Besides, it seems to be another good alternative to modify HA with a small-molecular ligand to further enhance the targeting of HA vehicle.…”
Section: Dual-ligand Modification To Further Enhance Active Targetingmentioning
confidence: 96%
“…This indicated that Bio-GC/5-FU nanoparticles allowed the delivery of more 5-FU into hepatoma carcinoma cells via the biotin receptor and regulated the complex intracellular signal conduction by 5-FU to achieve significant inhibitory effects on the migration of liver cancer cells [39]. CS, galactose, and biotin have good biological compatibility and degradability, and have no obvious toxic side effects [40][41][42]. We synthesized Bio-GC nanomaterials and tested the toxicity of the Bio-GC nanomaterials.…”
Section: Discussionmentioning
confidence: 99%